Developing processing windows for powder pre-heating in electron beam melting. (November 2022) - Lin, Zeyu; Dadbakhsh, Sasan; Rashid, Amir
Abstract: Powder pre-heating is a critical step in electron beam melting (EBM), while there has been no systematic work to study the corresponding processing windows so far. Accordingly, this work investigates the relation between the sintering and the issues appearing during pre-heating (e.g., smoking or excessive sintering) in EBM of highly susceptible-to-smoke Nickel-Titanium (NiTi) powder. First, the EB spot size was assessed depending on different focus offsets and beam currents from beam tracking experiments on a ceramic-coated stainless steel plate. Afterwards, the smoke tests were carried out at different focus offsets and beam currents in terms of beam speeds. It is shown that a smaller EB spot can effectively prevents smoking by enhancing the sintering degree. However, since this high sintering degree can cause strong powder bonding preventing the powder recycling, less focused beam (or larger EB spot) was selected to reach medium but efficient sintering in the level of around 30 %. Moreover, due to the influence of the diverging angle on the EB-material interaction, it is found that the negative defocused EB mitigates the smoke phenomenon compared to the positive defocused EB with a similar spot size. Based on the smoke test results, linked to the sintering degree, the processing windows for pre-heating NiTi powder are developed demonstrating three different modes: smoke-heating, melting-heating and healthy-heating.